The role and regulation mechanism of Chinese traditional fitness exercises on the bone and cartilage tissue in patients with osteoporosis: A narrative review - Sun, Weibo; Zhang, Xin-An; Wang, Zhuo (Frontiers in Physiology, 2023)
Osteoporosis (ops) is a systemic degenerative bone disease characterized by bone mass reduction, bone mineral density loss, bone microstructure destruction, bone fragility, and increased fracture susceptibility. Thus far, drug therapy is the main method used to prevent and treat osteoporosis. However, long-term drug treatment will inevitably lead to drug resistance and certain side effects. In response, rehabilitation treatment is generally recommended, which involves drug supplementation combined with the treatment. A Chinese traditional fitness exercise is an organic combination of sports and traditional Chinese medicine with a series of advantages such as being safe, convenient, non-toxic, and harmless. Hence, it is one of the rehabilitation methods widely used in clinical practice. By searching the CNKI, PubMed, Web of Science, Embase, Cochrane Library, and other relevant databases, our research clarifies the current situation of four kinds of Chinese traditional fitness exercises widely used in clinical practice, namely, Taijiquan, Baduanjin, Wuqinxi, and Yijin Jing. In addition, the molecular mechanism of osteoporosis is summarized in this study. Based on the research, Chinese traditional fitness exercises are expected to directly stimulate the bone through a mechanical load to improve bone density. Moderate and regular traditional Chinese fitness exercises also improve osteoporosis by regulating the endocrine system with the secretion of hormones and factors such as estrogen and irisin, which are beneficial for bone formation. Finally, the purpose of promoting bone formation, reducing bone loss, and preventing and treating osteoporosis is achieved. The various means of Chinese traditional fitness exercises have different emphases, and the effect of improving bone density differs in various parts of the body. The exercisers may choose the exercise flexibly based on their own needs. Chinese traditional fitness exercises can improve the bone density of the exercisers and relieve pain, improve balance, and regulate the psychological state. Consequently, it is worth promoting to be applied in clinical practices.